Dashboard-Based Tourism Data Visualization In Jambi Province Using The Seven Stages Of Visualizing Data - Muhammad Nabil; Pradita Eko Prasetyo Utomo; Rizqa Raaiqa Bintana (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Tourism is a global and national priority sector that holds significant potential in Jambi Province, supported by its rich natural and cultural heritage. To support effective development strategies, the availability of accurate, accessible, and informative data is fundamental. Although the Jambi Open Data Website has presented a tourism dashboard, observations indicate that the visualizations are statistical in nature, lack comprehensiveness, and fail to present in-depth patterns or trends, thus limiting their utility as a decision-making tool. This study aims to address this gap by developing a more interactive, informative, and analytical tourism data visualization dashboard for Jambi Province using Tableau. The methodology used is The Seven Stages of Visualizing Data by Ben Fry (2008), which systematically combines data processing and visual design, including Acquire, Parse, Filter, Mine, Represent, Refine, and Interact. The result is the development of three functional dashboards: Tourist and Attraction, Hotel Accommodation, and Tourism Business, with functional validation using Black Box Testing. The main findings revealed by the dashboards are the presence of significant geographic regularities; Although Kerinci Regency recorded the highest number of attractions (135), Jambi City dominates in terms of tourist arrivals (4.258 million) and the concentration of hotel infrastructure (196 hotels) and tourism businesses (605 Creative Economy businesses). The Creative Economy sector is dominated by Culinary and Crafts. The conclusion of this study is that the application of the Seven Stages framework has proven effective in producing a valid and analytical system, providing clearer insights into the dynamics of Jambi tourism and supporting evidence-based policy formulation.